Blockade of endothelin receptors attenuates end-organ damage in homozygous hypertensive ren-2 transgenic rats - Dvorák, Pavel; Kramer, Herbert J; Bäcker, Angela; Malý, Jan; Kopkan, Libor; Vanecková, Ivana; Vernerová, Zdena; Opocenský, Martin; Tesar, Vladimír; Bader, Michael; Ganten, Detlev; Janda, Jan; et al. (Kidney & blood pressure research, 2004)
BACKGROUND/AIMS: A growing body of evidence suggests that the interplay between the endothelin (ET) and the renin-angiotensin systems (RAS) plays an important role in the development of the malignant phase of hypertension. The present study was performed to evaluate the role of an interaction between ET and RAS in the development of hypertension and hypertension-associated end-organ damage in homozygous male transgenic rats harboring the mouse Ren-2 renin gene (TGRs) under conditions of normal-salt (NS, 0.45% NaCl) and high-salt (HS, 2% NaCl) intake. METHODS: Twenty-eight-day-old homozygous male TGRs and age-matched transgene-negative male normotensive Hannover Sprague-Dawley (HanSD) rats were randomly assigned to groups with NS or HS intake. Nonselective ET(A/B) receptor blockade was achieved with bosentan (100 mg/kg/day). Systolic blood pressure (BP) was measured in conscious animals by tail plethysmography. Rats were placed into metabolic cages to determine proteinuria and clearance of endogenous creatinine. At the end of the experiment the final arterial BP was measured directly in anesthetized rats. Kidneys were taken for morphological examination. RESULTS: All male HanSD fed either the NS or HS diet exhibited a 100% survival rate until 180 days of age (end of experiment). The survival rate in untreated homozygous male TGRs fed the NS diet was 41%, which was markedly improved by treatment with bosentan to 88%. The HS diet reduced the survival rate in homozygous male TGRs to 10%. The survival rate in homozygous male TGRs on the HS diet was significantly improved by bosentan to 69%. Treatment with bosentan did not influence either the course of hypertension or the final levels of BP in any of the experimental groups of HanSD rats or TGRs. Although the ET-1 content in the renal cortex did not differ between HanSD rats and TGRs, ET-1 in the left heart ventricle of TGRs fed the HS diet was significantly higher compared with all other groups. Administration of bosentan to homozygous male TGRs fed either the NS or HS diet markedly reduced proteinuria, glomerulosclerosis and attenuated the development of cardiac hypertrophy compared with untreated TGR. CONCLUSIONS: Our data show that nonselective ET(A/B) receptor blockade markedly improves the survival rate and ameliorates end-organ damage in homozygous male TGRs without significantly lowering BP.
Keywords: Endothelin-1; antagonisté endotelinového receptoru; velikost orgánu; proteinurie; Proteinuria; Electrolytes; renin; Homozygote; kreatinin; Sodium, Dietary; geneticky modifikovaná zvířata; ledviny; sulfonamidy; endotelin-1; Kidney; krysa rodu Rattus; bosentan; Antihypertensive Agents; sodík dietní; zvířata; Creatinine; renální hypertenze; Bosentan; Endothelin Receptor Antagonists; Renin; homozygot; Animals, Genetically Modified; potkani Sprague-Dawley; krevní tlak; Hypertension, Renal; Male; elektrolyty; Rats; Rats, Sprague-Dawley; Animals; Organ Size; antihypertenziva; mužské pohlaví; Blood Pressure; Sulfonamides